PEMENUHAN HAK MASYARAKAT DALAM PENGURUSAN DOKUMEN KEPENDUDUKAN DI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR DI TINJAU DARI UNDANG-UNDANG NOMOR 24 TAHUN 2013 TENTANG ADMINISTRASI KEPENDUDUKAN - Ridho Hanif Farza; Firdaus Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Of the several people who have taken care of the Family Card and Electronic Identity Card, the processing only takes 14 working days. However, during that time, the community members paid the government officials or brokers from the community to administer the Family Card and Electronic Identity Card in the amount of Rp. 300,000, - (three hundred thousand rupiah) for the Family Card and Rp. 250.000,- (two hundred and fifty thousand rupiah) for one Electronic Identity Card. This study uses a sociological juridical approach. Sociological juridical research or empirical research is an approach by looking at the reality that occurs in the field. While the nature of the research is descriptive which aims to provide a clear picture of the problem being studied.The fulfillment of community rights in managing population documents in Tanah Putih Subdistrict, Rokan Hilir Regency has not been achieved optimally because the process in managing population documents takes a long time on the grounds that the blank population service has run out. As well as illegal levies carried out by unscrupulous persons for the administration of population documents. Meanwhile, in Article 79A of Law Number 24 of 2013 concerning Population Administration, the administration and issuance of population documents is free of charge. Obstacles in fulfilling community rights in managing population documents in Tanah Putih Subdistrict, Rokan Hilir Regency, namely due to delays in issuance since the applicant requested it or more than 14 workingdays. This is due to the process of signing the Family Card (KK) which must be signed by the Head of the Population and Civil Registration Office of Rokan Hilir Regency and cannot be represented, while delays in the electronic Identity Card (KTP-el) are caused by the unavailability of blank e-KTPs. at the Population and Civil Registration Office of Rokan Hilir Regency.